Head rebound test in the clinical neurological examination of veterinary patients: a case example and discussion of Stewart and Holmes’ rebound phenomenon - Santifort, Koen M. (Frontiers in Veterinary Science, 2023)
In human medical neurology, the clinical neurological examination is variably augmented by specific tests that may be either unsuitable for veterinary patients or not included in the clinical evaluation of veterinary neurological patients due to clinicians being unfamiliar with these tests. An example of the latter can be found in testing for the Stewart & Holmes’ rebound phenomenon (‘rebound test’). In this article, a veterinary case example is presented in which a modified version of this test was performed (‘head rebound test’). The interpretation of the results of this test is discussed and the literature on the Stewart & Holmes’ rebound phenomenon and testing thereof is reviewed.